THE INFLUENCE OF CORONARY BYPASS ON ENDOTHELIAL AND ERECTILE DYSFUNCTION IN ISCHEMIC HEART DISEASE - S. A. Pomeshkina; E. V. Pomeshkin; T. Yu. Sergeeva; I. N. Sizova; O. L. Barbarash (Российский кардиологический журнал)
Aim. To evaluate coronary bypass grafting under artificial circulation conditions on endothelial and erectile dysfunction in patients with ischemic heart disease (CHD). Material and methods. Totally 117 patients participated in the study, with stable CHD at the mean age 55,8±5,3 y.  o.,  planned to CBG. In all patients we used questionnaire “International Index of Erectile dysfunction” (IIED), registration of nocturnal penile tumescenses (NPT), post compression tests on brachial and cavernous arteries. All patients were divided into two groups, those with and without erectile dysfunction (ED) (n=60, n=57, resp.). Results. By the results of the investigation in patients with ED after CBG there was significant worsening of erectile function. It was found, that the existence of ED before operation is an important prognostic factor for its progression after the operation. Others, with non-affected erectile function, after the operation had higher chances to save it. Even more, it was found that in patients without preoperational ED by 6 months after CBG there was tendency to improvement of EZVD comparing with baseline values, but in group with ED this tendency was not found. Also in patients without ED in all stages of study there was significantly better vasoregulating function of endothelium on brachial artery comparing to ED patients. The same tendency was found and on cavernous arteries. While analyzing the prevalence of cardiovascular events after CBG it was found that in ED group 4 patients (7%) cardiovascular events developed, but without ED — did not. Conclusion. So the presence of ED might be a significant marker of worse outcome in CHD patients, underwent CBG.